2023
DOI: 10.1021/acs.orglett.3c00966
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Vinylogous Dearomatization

Abstract: The first vinylogous dearomatization is reported. Under a photoinduced platform, various benzothiophenes functionalized by ketones at the 3-position could react with 3-methylenechroman-4-ones efficiently, leading to a variety of valuable products that contain the pharmaceutically significant chromones and 2,3-dihydrobenzo­[b]­thiophenes concurrently. The transformations were revealed to experience hydrogen-atom transfer, dearomatization, olefin migration, and radical cross coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Jiang et al recently reported first vinylogous dearomatization of ketone functionalized benzothiophenes with chromanone derivatives for the synthesis of 1,6-dicarbonyl compounds (Scheme 58). [103] As per the plausible reaction mechanism, upon irradiation of blue LED benzothiophene 81 generates its triplet state 81* via intersystem crossing (ISC), which then undergoes hydrogen atom transfer (HAT) with chromanone derivatives 82 and produces ketyl radical A and radical B. Subsequently, A undergoes dearomatization to generate radical D and B produces radical C via olefin isomerization.…”
Section: Synthesis Of 16-/17-dicarbonylsmentioning
confidence: 99%
“…Jiang et al recently reported first vinylogous dearomatization of ketone functionalized benzothiophenes with chromanone derivatives for the synthesis of 1,6-dicarbonyl compounds (Scheme 58). [103] As per the plausible reaction mechanism, upon irradiation of blue LED benzothiophene 81 generates its triplet state 81* via intersystem crossing (ISC), which then undergoes hydrogen atom transfer (HAT) with chromanone derivatives 82 and produces ketyl radical A and radical B. Subsequently, A undergoes dearomatization to generate radical D and B produces radical C via olefin isomerization.…”
Section: Synthesis Of 16-/17-dicarbonylsmentioning
confidence: 99%